Bibliometric Analysis of Procurement Ethics and Supplier Management - Judijanto, Loso; Hamzali, Said; Utami , Eva Yuniarti (Westscience Press, 2025)
This study conducts a bibliometric analysis to map the intellectual structure, thematic trends, and collaborative patterns within the field of procurement ethics and supplier management. Using data from the Scopus database and visualized through VOSviewer, the analysis covers co-authorship networks, keyword co-occurrence, citation structures, and country-level collaboration. Results show that